2022
DOI: 10.3389/fphar.2022.882197
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Antitumoral Effects of Linseed Oil and Its Combination With Doxorubicin

Abstract: Linseed oil (LO) is known for its exceptional nutritional value due to the high content of alpha-linolenic acid (ALA), an essential omega-3 polyunsaturated fatty acid; its anticarcinogenic effect has been established in several experimental and epidemiological studies. As an adjuvant of chemotherapeutic agents, LO and other ALA-rich vegetable oils have been studied in only a handful of studies at the experimental level. However, the efficacy of antitumoral therapy using doxorubicin (Dox) in combination with AL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…One of the most commonly used chemotherapeutic agents for treating breast cancer and other solid tumors is DOX. The effectiveness of a combination treatment between DOX and natural agents was reported against cancer [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…One of the most commonly used chemotherapeutic agents for treating breast cancer and other solid tumors is DOX. The effectiveness of a combination treatment between DOX and natural agents was reported against cancer [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…injection on the 5th day after tumor transplantation. The choice of the doxorubicin dose in our study was based on previous experiments conducted in a similar experimental model with rats, which demonstrated relative safety at a single dose of 5 mg/kg ( 48 , 49 ).…”
Section: Methodsmentioning
confidence: 99%
“…Doxorubicin (Dox) is a broad-spectrum antibiotic that can exert antitumor effects by increasing the levels of ROS in cells. Oleg Shadyro et al [ 94 ] reported that Dox combined with FO can not only reduce the intensity and volume of Pliss lymphosarcoma and Lewis lung adenocarcinoma but also inhibit Lewis lung adenocarcinoma metastasis. In addition, because PUFAs are components of the cell membrane, ALA may be used as a functional material for small molecule modification via coupling with antitumor drugs [ 95 ].…”
Section: Drug and Ala Combinations For Anticancer Effectsmentioning
confidence: 99%